Paratylenchus ilicis n. sp. (Nematoda: Paratylenchinae) Associated with Holly from the Netherlands and New Taxonomical and Phylogenetic Support for the Synonymization of Cacopaurus with Paratylenchus - Rolish Singh Phougeishangbam; Lokker Bram; Couvreur Marjolein; Bert Wim; Karssen Gerrit (Journal of Nematology, 2022)
Paratylenchus ilicis n. sp. was found associated with holly in the Netherlands and was described based on morphology, morphometrics, rRNA and mitochondrial cox1 genes, phylogenetic relationships with other Paratylenchus species, host information and geographical distribution. This species can be morphologically diagnosed based on its light brown, slightly obese to obese females with tubercles on cuticle, lateral bands widening into an ovoid field around vulva level, stylet length of 70 μm to 100 μm, outstretched to reflexed ovary, rounded sperm-filled spermatheca, vagina opening into a thick-walled rounded space, absence of vulval flaps and vulva at 89% to 95% of body length, very short tail in all life stages, and a characteristic finger-like tail tip in juveniles (J2). The new species is morphologically closest to Cacopaurus pestis but differs based on the absence of a scutellum-like differentiation in the lateral field, the ovaries that can be outstretched or reflexed, and the finger-like tail tip in J2. Furthermore, both species were found to be molecularly distant from one another, found in different habitats, and are associated with different hosts. The high morphological similarity between Cacopaurus and Paratylenchus and our phylogenetic analyses, revealing that the former is embedded within different Paratylenchus clades and thus polyphyletic, provide new evidences for the synonymization of Cacopaurus with Paratylenchus.